Synthetic studies towards the marine natural product phorboxazole A - Tornos, James A. (1998)
The thesis describes synthetic studies towards the marine natural product phorboxazole A. This unprecedented compound was recently isolated from an Indian Ocean sponge and displays extraordinary levels of cytostatic activity against a broad range of human cancer cell lines. The Introduction summarises a variety of different natural products which have been targeted as anti-cancer agents, and compares their mode of action with that of phorboxazole A. A review of structurally related natural products is then included, followed by an account of how phorboxazole A was isolated and its structure determined. The Introduction concludes with a brief discussion on our planned retrosynthetic analysis and contemporaneous studies within our research group towards phorboxazole A.